2022
DOI: 10.3390/su14020943
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Blockchain Technology in the Electronic Commerce of Tourism Services: An Exploratory Study on Romanian Consumers

Abstract: Blockchain technology is considered one of the most revolutionary innovations that has much to offer the tourism industry, having a positive impact among consumers with the help of interactive applications but also easy to use. Tourist services must constantly evolve in a society where the consumer has everything a click away and his requirements are demanding when it comes to quality leisure. Blockchain technology has the power to change the course of the travel experience, offering the customer more autonomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…In addition to ticketing, effective inventory management, marketing, and advertising. This is indicated by previous studies (Barkel et al, 2021;Raluca-Florentina, 2022;Rashideh, 2020), This is indicated by previous studies (Barkel et al, 2021;Raluca-Florentina, 2022;Rashideh, 2020), which confirmed that blockchain has many unique uses in the hospitality industry.…”
Section: Reliability Analysissupporting
confidence: 74%
See 3 more Smart Citations
“…In addition to ticketing, effective inventory management, marketing, and advertising. This is indicated by previous studies (Barkel et al, 2021;Raluca-Florentina, 2022;Rashideh, 2020), This is indicated by previous studies (Barkel et al, 2021;Raluca-Florentina, 2022;Rashideh, 2020), which confirmed that blockchain has many unique uses in the hospitality industry.…”
Section: Reliability Analysissupporting
confidence: 74%
“…It is available to all people involved in this technology around the world. Therefore, the reviews will be real, verified, reliable, and from real customers (Raluca-Florentina, 2022;Caddeo and Pinna, 2021).…”
Section: Overview Of Blockchain Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…As noted in the study [9], the most important advantage of such a system is the creation of new forms of communication between the supplier and the consumer. In decentralized systems, there is no need for outside support to complete a transaction.…”
Section: Introductionmentioning
confidence: 99%